2019
DOI: 10.1096/fj.201801696rrrr
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of maternal UHRF1 severely reduces mouse oocyte quality and causes developmental defects in preimplantation embryos

Abstract: The ubiquitin‐like, containing PHD and RING finger domains, 1 (UHRF1) protein recognizes DNA methylation and histone modification and plays a critical role in epigenetic regulation. Recently, UHRF1 was shown to have a role in DNA methylation in oocytes and early embryos. Here, we reveal that maternal UHRF1 determines the quality of mouse oocytes. We generated oocyte‐specific Uhrf1‐knockout mice and found that females were sterile, and few maternal UHRF1‐null embryos developed into blastocysts. The UHRF1‐null o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…In the present study, scRNA-seq demonstrated that for in vitro and in vivo embryos, expression of chromatin factors and transcriptional factors had large differences, suggesting that the in vitro embryo culture system could significantly alter the gene expression and influence the developmental ability. For DNA methylation factors (UHRF1/2 and DNMT1/3A/3B), expression levels and changing trends were very different between in vitro and in vivo embryos, indicating that DNA methylation difference caused by these factors might possibly affect the transcription integrity 51 and preimplantation development 52 . Similar results for factors related to H3K4 methylation and transcription were also found to be different between in vitro and in vivo groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, scRNA-seq demonstrated that for in vitro and in vivo embryos, expression of chromatin factors and transcriptional factors had large differences, suggesting that the in vitro embryo culture system could significantly alter the gene expression and influence the developmental ability. For DNA methylation factors (UHRF1/2 and DNMT1/3A/3B), expression levels and changing trends were very different between in vitro and in vivo embryos, indicating that DNA methylation difference caused by these factors might possibly affect the transcription integrity 51 and preimplantation development 52 . Similar results for factors related to H3K4 methylation and transcription were also found to be different between in vitro and in vivo groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, UHRF1 gene polymorphisms are closely associated with oligospermia in Chinese men 44 . Although the process of oogenesis was not affected, a large proportion of the embryos derived from the Uhrf1 ‐knockout (KO) oocytes died before reaching the blastocyst stage, which might have been caused by a maternal effect 45,46 . However, the underlying mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…44 Although the process of oogenesis was not affected, a large proportion of the embryos derived from the Uhrf1knockout (KO) oocytes died before reaching the blastocyst stage, which might have been caused by a maternal effect. 45,46 However, the underlying mechanisms remain unknown. Our results showed that UHRF1 was localized in the cytoplasm of CTB, STB, and villi columns, and its expression was significantly decreased in the villi of patients with RPL.…”
Section: Myd88/nf-κb Signaling Pathway Promoted the Pro-inflammatory ...mentioning
confidence: 99%
“…Uhrf1 deficiency is reported to alter the epigenetic pattern of several target genes and consequently induce transcriptomic changes resulting in developmental abnormalities. Deletion of maternal Uhrf1 causes developmental defects in preimplantation embryos [34], while at pre-gastrulation stage, altered uhrf1 expression results in embryonic lethality [23]. Knockout of zebrafish uhrf1 and dnmt1 presented defects in lens formation and microphthalmia [24], while conditional Uhrf1 deficiency in mouse model increased the expression of several genes including Hspb1, a gene involved in chondrocyte differentiation [35] and suppressed osteoblast activity [36].…”
Section: Discussionmentioning
confidence: 99%